New open-loop recycling approaches for disposable diaper waste - Lim, Jee Khan; Müller, Julian; Mahdi, Fatin Norsuaidah; Chen, Soo Kien; Tan, Kar Ban; Lee, Oon Jew (Canadian Science Publishing, 2021)
Disposable diapers are considered indispensable hygiene products, which is reflected in their massive levels of consumption globally and waste generation. Most of the diaper waste is neither segregated nor treated and ends up in landfills or incinerators. The reported life cycle assessment highlights that the diaper waste is not solely generated after single-use but begins as early as the raw materials acquisition stage. Although what is done cannot be undone, diaper waste can be recycled. Diaper waste valorization has been explored on laboratory- and commercial-scales for years, with varying degrees of success. Leading diaper manufacturers such as Procter & Gamble, Kimberly–Clark, and Unicharm are making progress in establishing closed-loop recycling of used diapers and converting diaper waste into new diapers. However, the broad potential for possible new products made from diaper waste has yet to be fully exploited. This review focuses on the enormous promise of diaper waste from the perspective of emerging open-loop recycling pathways. We demonstrate that diaper waste can be harnessed and converted into nondiaper products, including energy pellets, anode material for lithium-ion batteries, concrete admixture, catalysts, soil amendment, and mushroom cultivation substrates. We also explore several active, commercial-scale diaper recycling approaches and provide a comprehensive blueprint to encourage open-loop recycling. Open-loop recycling is a practical strategy for managing diaper waste, rectifying environmental damage, and contributing to circular supply chains.